2021
DOI: 10.3390/vaccines9080873
|View full text |Cite
|
Sign up to set email alerts
|

Hesitant or Not Hesitant? A Systematic Review on Global COVID-19 Vaccine Acceptance in Different Populations

Abstract: Vaccination currently appears to be the only strategy to contain the spread of COVID-19. At the same time, vaccine hesitancy (VH) could limit its efficacy and has, therefore, attracted the attention of Public Health Systems. This systematic review aimed at assessing anti-COVID-19 vaccine acceptance rates worldwide and at identifying populations more prone to vaccine hesitancy, for which specific interventions should be planned. PubMed database was searched using a purposely formulated string. One hundred out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 128 publications
3
96
0
3
Order By: Relevance
“…In this multicenter study conducted at the beginning of the COVID-19 vaccination campaign in Italy, we found a high overall vaccine acceptance rate (75.6%), in line with other studies that detected VH in the general population during the same time period (70.9%–77.3%) [ 10 , 15 , 16 ]. Vaccine confidence rates were found to be not particularly different between the two regional capitals surveyed, with 79.3% and 72.1% for Palermo and Bologna, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this multicenter study conducted at the beginning of the COVID-19 vaccination campaign in Italy, we found a high overall vaccine acceptance rate (75.6%), in line with other studies that detected VH in the general population during the same time period (70.9%–77.3%) [ 10 , 15 , 16 ]. Vaccine confidence rates were found to be not particularly different between the two regional capitals surveyed, with 79.3% and 72.1% for Palermo and Bologna, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Even in the context of the COVID-19 vaccination campaign, vaccine hesitancy (VH), listed by the World Health Organization (WHO) as one of the ten global health threats of 2019, [ 6 ] and defined as “delayed acceptance or refusal of vaccination despite the availability of vaccine services” [ 7 ], played a key role. VH varies in form and intensity depending on where and when it occurs and which vaccine is affected, as confirmed by several studies and reviews on the topic [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 92%
“…Healthcare workers (HCWs) were prioritised to receive COVID-19 vaccines in most countries, due to the high occupational risk of COVID-19 infection [1][2][3][4]. Systematic reviews of the international literature report that HCW vaccine acceptance rates between countries varied between 28% and 96% (data published up to March 2021) [5,6] with hesitancy associated with vaccine safety (e.g., side effects), rapid development, and vaccine efficacy and effectiveness (data published up to February 2021) [7]. COVID-19 vaccine intentions [8,9] and vaccine uptake [10,11] also varies by clinical discipline and setting internationally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the acceptance of the COVID-19 vaccine among healthcare providers, students in health-related fields, and the general public showed that demographic factors of age, gender, and education were significantly associated with intention to use the vaccine [12]. In addition, individual perceptions regarding perceived infection risk, infection severity, and perceived vaccine risks and benefits are suggested predictors of vaccine acceptance and hesitancy [11,[15][16][17][18]. To our knowledge, this is the first study to report the vaccine acceptance rate and identify attitude and belief factors that underpin vaccination intentions among health science students in Morocco prior to the start of the national COVID-19 vaccination campaign.…”
Section: Introductionmentioning
confidence: 99%